Aluminum-induced high IAA concentration may explain the Al susceptibility in Citrus limonia - Silva, Carolina M. S. [UNESP]; Cavalheiro, Mariana F. [UNESP]; Bressan, Anna C. G. [UNESP]; Carvalho, Brenda M. O. [UNESP]; Banhos, Otavia F. A. A. [UNESP]; Purgatto, Eduardo; Harakava, Ricardo; Tanaka, Francisco A. O.; Habermann, Gustavo [UNESP] (Springer Nature, 2019)
In acidic soils (pH < 5.0), aluminum (Al) occurs as Al 3+ , which is phytotoxic and reduces the root growth by hormonal imbalance and/or cell wall rigidity. However, the explanations for the decrease in root growth are not clear. A 60-day study was held with ‘Rangpur’ lime (Citrus limonia) plants grown in nutrient solution containing 0 and 1480 µM Al. We measured plant biometric data and used root apices to analyze auxin (IAA), the expression of some Al-responsive genes that had been differentially expressed in a transcriptome analysis and anatomical profiles. We found up-regulated expression of multidrug and toxic compound exudation (Cl-MATE channel), citrate synthase (Cl-CS) and pectin methylesterase inhibitor (Cl-PMEI) genes, but while Cl-PMEI expression was increased after 7 days, Cl-CS and Cl-MATE were up-regulated only after 60 days, suggesting that the timing of these events was ineffective against Al. These results could be associated with the Al-induced decrease in root growth and anatomical root damage. In addition, genes related to IAA cell transport were not differentially expressed in the transcriptome analysis. Therefore, high IAA and up-regulation of auxin-related small RNAs suggest Al-induced high IAA concentration rather than Al-induced disruption in IAA distribution in root cells of this species.
Keywords: Al 3+; Auxin; Efflux channels; Gene expression; Root growth; ‘Rangpur’ lime